Global characterization of signalling networks associated with tamoxifen resistance in breast cancer. (19th August 2013) - Browne, Brigid C.; Hochgräfe, Falko; Wu, Jianmin; Millar, Ewan K. A.; Barraclough, Jane; Stone, Andrew; McCloy, Rachael A.; Lee, Christine S.; Roberts, Caroline; Ali, Naveid A.; Boulghourjian, Alice; Schmich, Fabian; et al.
<x xml:space="preserve">Abstract</x> Acquired resistance to the anti‐estrogen tamoxifen remains a significant challenge in breast cancer management. In this study, we used an integrative approach to characterize global protein expression and tyrosine phosphorylation events in tamoxifen‐resistant MCF7 breast cancer cells (TamR) compared with parental controls. Quantitative mass spectrometry and computational approaches were combined to identify perturbed signalling networks, and candidate regulatory proteins were functionally interrogated by siRNA‐mediated knockdown. Network analysis revealed that cellular metabolism was perturbed in TamR cells, together with pathways enriched for proteins associated with growth factor, cell–cell and cell matrix‐initiated signalling. Consistent with known roles for Ras/MAPK and PI3‐kinase signalling in tamoxifen resistance, tyrosine‐phosphorylated MAPK1, SHC1 and PIK3R2 were elevated in TamR cells. Phosphorylation of the tyrosine kinase Yes and expression of the actin‐binding protein myristoylated alanine‐rich C‐kinase substrate (MARCKS) were increased two‐ and eightfold in TamR cells respectively, and these proteins were selected for further analysis. Knockdown of either protein in TamR cells had no effect on anti‐estrogen sensitivity, but significantly decreased cell motility. MARCKS expression was significantly higher in breast cancer cell lines than normal mammary epithelial cells and in ER‐negative versus ER‐positive breast cancer cell lines. In primary breast cancers, cytoplasmic MARCKS staining was significantly higher in basal‐like and HER2 cancers than in luminal cancers, and was independently predictive of poor survival in multivariate analyses of the whole cohort (P < 0.0001) and in ER‐positive patients (P = 0.0005). These findings provide network‐level insights into the molecular alterations associated with the tamoxifen‐resistant phenotype, and identify MARCKS as a potential biomarker of therapeutic responsiveness that may assist in stratification of patients for optimal therapy.